Training for minor surgery in general practice during preregistration surgical posts. - Pringle, M (1991)
OBJECTIVE--To study the teaching of minor surgery to preregistration house officers in surgery and their confidence in their skills. DESIGN--Questionnaire survey of consultants and vocational trainees. SETTING--Trent, Oxford, and East Anglian Regional Health Authorities. SUBJECTS--All consultant surgeons (n = 148) with preregistration house officers on their firm and all first year vocational trainees in general practice (n = 165). MAIN OUTCOME MEASURES--Time spent teaching minor surgery to preregistration house officers; source of teaching; trainees' confidence in their skills in 15 minor surgical procedures and degree of confidence that consultants expected their junior house officers to achieve. RESULTS-- 137 (93%) consultants and 139 (84%) vocational trainees replied; 131 of the consultants' replies and all the trainees' replies were analysable. Only 14 consultants had a curriculum for teaching junior house officers, and 90 offered less than four hours' teaching a week. Only 11 trainees thought that their firm had had a curriculum, and 102 reported having received under two hours' teaching a week. The consultants indicated that they did most of the teaching, but the trainees reported having received most of their teaching from junior registrars. Seventy nine consultants attempted to teach minor surgery. They expected their junior house officers to acquire greater confidence in their skills in minor surgery than did the other consultants, but overall the confidence expected was low. The trainees were more confident than the consultants expected them to be, but overall confidence was still low. Those who had received more teaching were significantly more confident. CONCLUSIONS--The educational potential of the post of preregistration house officer in surgery seems underexploited, particularly with regard to teaching skills in minor surgery.